The Potential of Plant Starch as A Natural Indicator in Practice of Iodometric Titration - Elfa, Noor; Sholahuddin, Arif; Suyidno, Suyidno (Universitas Lambung Mangkurat, 2025)
Iodometric titration generally uses synthetic starch as an endpoint indicator. This indicator is non-biodegradable, environmentally unfriendly, and relatively expensive. An alternative that can be offered is the use of natural starch from local plants as a more sustainable indicator. This study aims to test the potential of starch from various plant sources as a natural indicator in iodometric titration. Analysis of copper levels using starch indicators from four local plants showed varying values, namely sticky rice 0.50 g, purple sweet potato 0.95 g, unus rice 0.67 g, potato 0.87 g, and, as a comparison, commercial synthetic starch indicators produced 0.58 g. Of the four starch sources, the glutinous rice starch indicator produced results closest to the synthetic indicator, with a difference of only 0.08 g. These findings indicate that glutinous rice starch has accuracy comparable to synthetic indicators, making it a potential alternative for effective iodometric titration indicators. Glutinous rice starch has the potential to be used as an effective, environmentally friendly, and more sustainable natural indicator compared to synthetic starch in iodometric titration.